Dimensional Changes in Extraction Sockets: A Pilot Study Evaluating Differences between Digital and Conventional Impressions - Min-Woo Baek; Hyun-Chang Lim; Kwantae Noh; Seong-Ho Choi; Dong-Woon Lee (Applied Sciences, 2022)
Traditionally, soft tissue records are obtained by dental impression using impression materials; however, accurately recording the soft tissue immediately after tooth extraction is difficult. We measured the tissue changes after tooth extraction and compared two impression modalities (digital versus conventional) by measuring the changes at the soft tissue level. In this case, 15 patients with 17 single extraction sites were enrolled. Conventional impression (CI) using vinyl polysiloxane material and digital impression (DI) using an intraoral scanner were prepared immediately after extraction (T0) and at 2 months post-extraction (T1). Standard tessellation language files were generated for superimposition of the tissue surface. The tissue changes and discrepancies were measured on the superimposed surfaces. The differences in the changes and the discrepancy between the tissue surface impression at each time point were compared. At all measuring levels, the total tissue change was significantly different between groups DI and CI (p < 0.05). DI exhibited a more pronounced tissue surface at both time points, and the total discrepancy was statistically significantly greater at T0 than at T1 (p < 0.05). The values from DI and CI demonstrated small but significantly different for the same study material. The interpretation of such differences may depend on the clinical situation or scientific value.